Managing Cellphone Services for Customer Satisfaction: Evidence from the Base‐of‐the‐Pyramid Markets. Issue 2 (19th November 2020) - Khuntia, Jiban; Mayya, Raveesh; Mithas, Sunil; Agarwal, Ritu
Abstract : This study investigates how value‐added services (VAS) and customer care services (CCS) moderate the association between satisfaction with the core telephone service and overall customer satisfaction in base‐of‐the‐pyramid (BOP) markets. We propose that customers respond to VAS and CCS differently due to variations in price evaluations of these services. We further examine how the interactions among the service dimensions may differ for local and global telephone providers. We used an archival dataset from a survey of more than 3200 cellphone customers across 34 providers in seven South Asian countries that include India, Pakistan, Bangladesh, Srilanka, Nepal, Bhutan, and Maldives to test our conjectures. We find that satisfaction with VAS negatively moderates the relationship between core connection satisfaction and overall satisfaction, and satisfaction with CCS positively moderates the relationship between core connection satisfaction and overall satisfaction. Furthermore, the positive and negative interaction effects are stronger for global vs. local providers. We discuss contributions and managerial implications of the findings.